2014
DOI: 10.1007/s00213-014-3809-6
|View full text |Cite
|
Sign up to set email alerts
|

Sigma 1 receptor activation regulates brain-derived neurotrophic factor through NR2A-CaMKIV-TORC1 pathway to rescue the impairment of learning and memory induced by brain ischaemia/reperfusion

Abstract: Sig-1R activation showed an attenuation in the ischaemia/reperfusion model and the activation of Sig-1R increased the expression of BDNF, possibly through the NR2A-CaMKIV-TORC1 pathway, and Sig-1R agonists might function as neuroprotectant agents in vascular dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 53 publications
2
36
0
1
Order By: Relevance
“…In the present study, after the administration of Sig-1R agonist PRE-084, the anxiety-like behaviors and cognitive impairments were significantly reversed, indicating therapeutic benefits of activating the Sig-1R pathway. A large number of studies have shown that Sig-1R activation yields a neuroprotective effect in a variety of diseases, such as ischemia/reperfusion, Alzheimer's disease, and pain [12,13,35,36]. However, Yin et al reported that Sig-1R deficiency reduced ß-amyloid-induced hippocampal neuronal cell death and cognitive deficits, contrary to the mainstream results [37].…”
Section: Harvey Et Al Reported That Stress-restress Evoked a Complexmentioning
confidence: 91%
See 2 more Smart Citations
“…In the present study, after the administration of Sig-1R agonist PRE-084, the anxiety-like behaviors and cognitive impairments were significantly reversed, indicating therapeutic benefits of activating the Sig-1R pathway. A large number of studies have shown that Sig-1R activation yields a neuroprotective effect in a variety of diseases, such as ischemia/reperfusion, Alzheimer's disease, and pain [12,13,35,36]. However, Yin et al reported that Sig-1R deficiency reduced ß-amyloid-induced hippocampal neuronal cell death and cognitive deficits, contrary to the mainstream results [37].…”
Section: Harvey Et Al Reported That Stress-restress Evoked a Complexmentioning
confidence: 91%
“…Not only is Sig-1R agonist regarded as one of the most efficient neuroprotective drugs, a body of evidence also exists of its beneficial effects in many disorders caused by disturbances of intercellular signaling pathways, particularly those associated with neurotrophic factors [11][12][13]. It is suggested that there is a direct relationship between Sig-1R agonists, Sig-1Rs and MAPKs and their possible roles in Sig-1R-mediated neuroprotection.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The Morris water maze (MWM) test was performed after the novel object recognition test as in our previous report [13]. The MWM consisted of a circular pool (100 cm in diameter and 50 cm in height) that was filled with water (25±1 ºC and 30 cm in depth).…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…This test was conducted as previously described (Le et al, 2015;Yamada et al, 2011;Xu et al, 2015) with minor modifications. Briefly, each mouse was first habituated to the test arena (W 25 Â L 35Â H 40 cm) for 10 min/day for 3 days.…”
Section: Behavior Testing Analysismentioning
confidence: 99%